O impacto do SINAES nas universidades privadas do Rio de Janeiro sob a perspectiva da teoria institucional: o curso de administração - Ferreira, Tereza Cristina dos Reis (2018)
Starting from the 1990’s, Brazil developed several strategies and policies of evoluation for higher education. It was implemented the Program of Institutional Evaluation of Brazilian Universities (PAIUB) in 1993, the National Courses’ Exam (ENC) in 1995. In 2004, Law No. 10,861 established the National System of Higher Education Evaluation (SINAES) in order to ensure the evaluation aimed at mapping higher education institutions (IES) in three dimension: evaluation of the institution, course evaluation. This study is located in the second dimension – course evaluation – and it intends to identify the impact of the current regulatory policy of higher education, formulated by SINAES in the Administration Course under the perception of institutional theory. In relation to Institutional Theory, the emphasis was on the phenomena such as institutional isomorphism and the consequent reduction of the diversity of the segment. As samples for this qualitative study, four private universities located in Rio de Janeiro were selected. The selection of Universities was made based on criteria of academic organization, administrative nature, offer bachelor’s degree in Administration since the implementation of SINAES, geographical location and year of foundation. Through a qualitative approach, with subsequent application of the content analysis technique, the data collection was performed with semi-structured interviews with the CPA (Overall Evaluation Committee) presidents with the coordinators of the administration course of these universities, and evidence was searched to show the existence of isomorphisms and at the end it is shown the presentation of the results. The targeted interviews were conducted and recorded in loco. It was also necessary bibliographic research on the subject, in a way that could help explain the studied phenomenon. Based on the analysis and interpretation of the data, it was confirmed that the impact of SINAES is strongly influenced by the State’s regulation of Universities, in which results in the homogenization of the institutional field. The administration courses are shaped to certain extent by a minimum curriculum of knowledge required by bodies such as the category council and the governing body of education of the State.